(3MGTjI TQM GdTeSjIs - (3GdjROj, YHO Gddg Hf GdMSjf Hf YHO Gddg, J (B1015 (3g`s ((3Ndjd Hf eMehOs)
(3ChdgG (B:s
(3GdMeO ddg GdPj dWa HMceJg YLGFH UfYJg(B... (3CeG HYO, agPg MbGFb dGFMI hObGFb SGfMI Ydi MGTjI GdefWb aj GdJgPjH GdJj CdagG(B... (3TgGH GdOjf(B...s
(3BNQgG (B:s
(3bhd(B: (3hfbjV GdVQhQ GdSGdH(B. (3Cj fbV GdVQhQI GdeWdbIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B: (3L(B2(3, U(B239s
(3GdPQjYI, HQbe(B: 378s
(3eYLe GdeDdajf(B: (3L(B2(3, U(B239s
(3GdPQjYI, HQbe(B: 378s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs